Pengaruh Literasi Keuangan, Kontrol Diri, dan Media Sosial Terhadap Perilaku Konsumtif Mahasiswa Ekonomi, Manajemen, dan Bisinis Kampus Negeri di Surabaya - Latifah, Vania Arin; Paramita, R A Sista (Jurnal Ilmiah Wahana Pendidikan, 2023)
Indonesia is in third place with a high level of consumerism. This consumptive behavior is supported by a digital culture that is growing every time. The level of consumerism is influenced by two factors, namely internal factors including the lack of ability about individual financial planning for financial management and external factors, namely purchasing goods via the internet such as shopping online or online shopping. This study aims to analyze the influence of financial literacy, self-control, and social media on the consumptive behavior of economics, management, and business students at state campuses in Surabaya. This type of research is quantitative which is obtained online via gform to 217 students. The data analysis technique used is multiple linear regression analysis using IBM SPSS version 25. The results of the study are that financial literacy variables have no effect on student consumptive behavior, self-control variables have a negative and significant influence on student consumptive behavior, and social media variables have a positive and significant influence on student consumptive behavior.